Adaptation of Student Socio-Religious Rituals and Practices during a Pandemic - Irmi Yunika Irmi; Eko Rangga Maulana; Saepulloh Pikri Saepulloh; wahyudi; Anas Prasetyo; Masduki Asbari; Dewiana Novitasari; Agus Purwanto (Journal of Information Systems and Management (JISMA), 2022)
The purpose of this community service activity is to provide knowledge to couples and prospective young married couples among students at a private university in Tangerang. The Covid-19 pandemic in Indonesia for approximately 2 years has changed all social and religious activities of the community, including the education segment, especially students. The fact that all educational activities must be carried out in remote situations in person has also changed their worship activities and socio-religious practices. Students fill their free time during distance learning with worship activities and social activities at home. This article elaborates on how students adapt to religion during a pandemic. The research was conducted using a qualitative approach, data collection techniques through in-depth interviews with 18 student informants and strengthened with virtual data through google forms. The results showed that students' religious adaptations in worship practices and social activities have helped increase their spirituality and closeness to religion. This is evidenced by the increase in the quantity of worship such as the intensity of reading the Qur'an, discipline in compulsory prayers, and student involvement in religious-based charity activities in the community.